Documentary weaving memories, building territories: La práctica artesanal en el municipio de Tocaima, Cundinamarca, como producción de conocimiento - Ariza Rodríguez, Cindy Mariana; Pulecio Bazurto, María Otilia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The conceptualization of artisan knowledge is complex and requires epistemological recognition within the sociocultural and economic context in which the artisan operates, where it is necessary to highlight the ancestral value, since, within learning there is a transfer of traditional knowledge when there is no break in the production of meaning that is constituted. That is why, this research seeks through a documentary, to make visible the work carried out by the artisans and basket makers of the municipality of Tocaima, Cundinamarca, managing to build an integration and training space where the basket makers are the ones who benefit and manage to transmit the knowledge. of the basketry.